2021
DOI: 10.1667/rade-20-00150.1
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet with Concurrent Chemoradiation in Head and Neck Squamous Cell Carcinoma: Preclinical and Phase 1 Trial Results

Abstract: Ketogenic diets (KD) are high in fat and low in carbohydrates, forcing cells to utilize mitochondrial fatty acid oxidation for energy production. Since cancer cells demonstrate increased mitochondrial oxidative stress relative to normal cells, we hypothesized that a KD may selectively enhance metabolic oxidative stress in head and neck cancer cells, sensitizing them to radiation and platinum-based chemotherapy without causing increased toxicity in surrounding normal tissues. This hypothesis was tested in precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In an uncontrolled phase I study, Ma et al. found that two thirds of HNSCC patients did not manage to consume a KD during 5 weeks of radiochemotherapy [ 25 ]. Thereby, all patients had received a PEG tube prior to the study, which was used to provide a ketogenic formula that accounted for the main calories of the KD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an uncontrolled phase I study, Ma et al. found that two thirds of HNSCC patients did not manage to consume a KD during 5 weeks of radiochemotherapy [ 25 ]. Thereby, all patients had received a PEG tube prior to the study, which was used to provide a ketogenic formula that accounted for the main calories of the KD.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, all patients had received a PEG tube prior to the study, which was used to provide a ketogenic formula that accounted for the main calories of the KD. Reasons for discontinuation included fatigue, nausea, and vomiting, two cases of grade 4 hyperuricemia, and one case of acute grade 3 pancreatitis; the attribution of these side effects to the KD was unclear in all cases [ 25 ]. Thus, a KD—even if applied via a PEG tube—may not be feasible in the general HNC population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KD might selectively enhance metabolic oxidative stress in head and neck cancer cells, and sensitize them to radiation and platinum chemotherapy without causing increased toxicity in surrounding normal tissues. This hypothesis was tested in preclinical murine xenografts in a previous study, mice bearing human head and neck cancer xenografts were fed either standard mouse chow or (a glucose-free diet) and exposed to ionizing radiation, Mice-bearing xenografts that received radiation and a glucose-free diet showed a slight improvement in tumor growth rate and survival compared to mice that received radiation alone (Ma et al, 2021), This is consistent with the conclusion of our research that showed that a glucose-free diet slightly prevents oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%